Debtor default in negative obligations: is it possible and appropriate to recognize it in the Peruvian Civil Code? - Vásquez Sotomayor, Aarón (2019)
This paper analyzes the current debtor default regime contained in the Peruvian Civil Code, in order to determine whether, despite the many voices against it, its applicable and appropriate for negative obligations. Based on a brief review of the debtor default regime and the nature of negative obligations, the authors scrutinize from a phenomenological and functional approach the opposing opinions to make these institutions compatible. Furthermore, based on an examination of the current status of the Peruvian Civil Code the authors argue that the application of the debtor default regime to negative obligations is not only possible but appropriate through an analog application of the current regime. Finally, they examine the regime proposed by the 2020 Draft Reform of the Peruvian Civil Code on the subject.